Genes related to the white face colour pattern in eight Russian cattle breeds - N. S. Yudin; N. M. Belonogova; D. M. Larkin (Вавиловский журнал генетики и селекции)
One of the major effects of domestication is change of animal coat colour to up to complete white colour of the whole body. It is possible that white colour of livestock animals had aesthetic significance for humans as well. The first step towards detection of genes and mutations controlling white colouring in animals is the genome-wide association studies. These studies, however, have not been done for the cattle breeds native to the Russian Federation. The aim of this study was therefore to identify genomic intervals and candidate genes that could be responsible for white face colouring in eight Russian cattle breeds. The data on genome-wide genotyping of 131,709 high-quality single nucleotide polymorphisms (SNPs) on 148 animas have been used in the program EMMAX. Association analysis has been performed using two related phenotypes: a) the white face with the rest of the body of any colour and b) white face with the rest of the body of different (non-white) colour. In the first case, the only statistically significant marker found was the SNP BovineHD0500019319 located on cattle chromosome (BTA) 5. The same SNP was the most significant within the cluster of three SNPs on BTA5: 68,803,879–69,365,854 associated also with the second phenotype. Five genes were found within this interval in the cattle genome, out of which the most likely functional candidate was SLC41A2, with the SNP BovineHD0500019319 found within its intronic sequence. SLC41A2 encodes a magnesium transporter protein. However, the function of this gene is not well established. Other members of this gene family are the key genes controlling differences in human skin and animal coat colour. Additional significant association signals with the second phenotype have been detected in BTA 1–4, 6–15, 18, 19, 24, 27, and 29. Overall, 37 genomic intervals have been detected associated with white face colouring in eight Russian native cattle breeds.